Lentinan-functionalized selenium nanoparticles induce apoptosis and cell cycle arrest in human colon carcinoma HCT-116 cells - Gao, Xiong; Yao, Yanting; Chen, Xujie; Lin, Xiaorong; Yang, Xiaobing; Ho, Chi-Tang; Li, Bin; Chen, Zhongzheng (Frontiers in Nutrition, 2022)
Selenium nanoparticles (SeNPs) have gained extensive attention for their excellent biological activity and low toxicity. However, SeNPs are extremely liable to aggregate into non-bioactive or gray elemental selenium, which limits their application in the biomedicine field. This study aimed to prepare stable SeNPs by using lentinan (LNT) as a template and evaluate its anti-colon cancer activity. The average particle diameter of obtained LNT-SeNPs was approximately 59 nm and presented zero-valent, amorphous, and spherical structures. The monodisperse SeNPs were stabilized by LNT through hydrogen bonding interactions. LNT-SeNPs solution remained highly stable at 4 ℃ for at least 8 weeks. The stability of LNT-SeNPs solution sharply decreased under high temperature and strong acidic conditions. LNT-SeNPs showed no obvious cytotoxic effect on normal cells (IEC-6) but significantly inhibited the proliferation of five colon cancer cells (HCT-116, HT-29, Caco-2, SW620, and CT26). Among them, LNT-SeNPs exhibited the highest sensitivity towards HCT-116 cells with an IC50 value of 7.65 µM. Also, LNT-SeNPs displayed better cancer cell selectivity than sodium selenite and selenomethionine. Moreover, LNT-SeNPs promoted apoptosis of HCT-116 cells through activating mitochondria-mediated apoptotic pathway. Meanwhile, LNT-SeNPs induced cell cycle arrest at G0/G1 phase in HCT-116 cells via modulation of cell cycle regulatory proteins. The results of this study indicated that LNT-SeNPs possessed strong potential application in the treatment of colorectal cancer.